Multiple myeloma presenting as proliferative (crescentic) glomerulonephritis. - Sirsat R (Journal of Postgraduate Medicine, 1994)
Glomerular extracapillary cellular proliferation with crescent formation initially presenting as rapidly progressive glomerulonephritis is a rare clinical manifestation of multiple myeloma. We report here a case of a 58 year old female who initially presented with haematuria, loss of weight and appetite and history of febrile episodes and was diagnosed following renal biopsy as rapidly progressive glomerulonephritis. Haemodialysis was carried out a month later because of uremic symptoms and maintained with monitoring of serum, calcium, phosphate, alkaline phosphatase, albumin and iPTH levels. After 6 months, she complained of bone pains over anterior chest wall which persisted even with low calcium haemodialysis. Serum protein electrophoresis and bone marrow aspiration revealed multiple myeloma. On starting chemotherapy, bone pain subsided but the patient expired within 15 days of therapy.